Transcriptomics Analysis Reveals Differences in Purine and Phenylpropanoid Biosynthesis Pathways Between Camellia sinensis var. Shuchazao and Camellia ptilophylla - Waqar Khan; Peng Zheng; Binmei Sun; Shaoqun Liu (Horticulturae)
Tea production and quality are largely determined by the many genetic and biochemical characteristics that occur in tea plant cultivars. Worldwide, tea is consumed for its pleasing and refreshing effects due to its caffeine content. The present study performed transcriptomics analyses of two tea species (Camellia sinensis var. Shuchazao (SCZ) and Camellia ptilophylla (CAF)) and identified diversity in the gene expression levels and major regulatory transcription factors (TFs) for the characterization of purine alkaloids and phenylpropanoid biosynthesis pathways. The RNA-seq analysis of two species (SCZ and CAF) revealed the differences in caffeine and catechins synthesis. In the purine alkaloid biosynthesis pathway, the S-adenosyl methionine (SAM) and adenosine monophosphate (AMP) pathway genes were significantly related to xanthosine synthesis in contrasting purine alkaloids among (Camellia sinensis var. Shuchazao (SCZ) and Camellia ptilophylla (CAF)). The significant expression of SAMS-5, PPAT-2, IMPDH-2, TCS-2, TCS-3, XMT-1, XMT-13, and XDH-4 in the xanthosine degradation pathway in CAF is attributed to higher theobromine content as compared to SCZ. Moreover, the transcription factors (TFs) AP2/ERF (20%), WRKY (12%), NAC (11%), and MYB (8%) were significantly correlated. The upregulated expression of caffeine synthesis genes in SCZ was correlated with MYB and AP2/ERF transcription factors. This study provides the basis for differences in the genetic mechanism in purine alkaloids, phenylpropanoid, and flavonoid biosynthesis pathways, which would be helpful in the development and selection of tea plant species with high or low caffeine concentrations. This study also provides a road map for future genetic improvement in tea species and cultivars.